2016
DOI: 10.1093/intqhc/mzv119
|View full text |Cite
|
Sign up to set email alerts
|

Patients' informational needs while undergoing brachytherapy for cervical cancer

Abstract: The article has identified women's informational needs providing a focus for patient-centred care. Providing patients with sufficient and understandable information could lessen feelings of fear and anxiety towards treatment delivery. Guidelines with a patient-centred approach could thus be developed to be used as a tool to assist members of multidisciplinary teams in providing quality care to this group of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
0
26
0
2
Order By: Relevance
“…There were 22 remaining articles. Five studies were randomised controlled studies (RCTs), 16,17,18,19,20 two case control studies, 21,22 nine cohort studies, 11,12,23,24,25,26,27,28,29 five qualitative studies 30,31,32,33,34 and 1 systematic literature review. 35…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 22 remaining articles. Five studies were randomised controlled studies (RCTs), 16,17,18,19,20 two case control studies, 21,22 nine cohort studies, 11,12,23,24,25,26,27,28,29 five qualitative studies 30,31,32,33,34 and 1 systematic literature review. 35…”
Section: Resultsmentioning
confidence: 99%
“…Of ten studies regarding psychological issues, nine reported that brachytherapy caused anxiety and distress for most women. 12,23,26,27,30,31,32,33,34 However Nail found the procedure was well tolerated without high levels of distress, depression or anxiety in most women. 28 Anderson et al described anxiety levels taking a long time to reduce, following completion of treatment.…”
Section: Anxiety and Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…No referido manual de orientações, foram contempladas, entre outras, orientações e informações sobre o procedimento em si, efeitos colaterais do tratamento, vida sexual e recomendações pós tratamento. Tais temas são relevantes e fundamentais para a preparação adequada da paciente, assim como observado em estudo anterior (22) acerca dos conhecimentos que as pacientes submetidas à braquiterapia ginecológica consideravam importantes e essenciais para um tratamento adequado.…”
Section: Discussionunclassified